Signet-ring cell carcinoma in rectal malignancies: a case report with an unexpected outcome - Long, Aichun; Huang, Cheng; Xu, Qinwei; He, Shasha; Zhang, Li; Zhang, Cuiwei (Frontiers in Oncology, 2025)
Signet ring-like cell prostate cancer is a rare and highly aggressive histological subtype of prostate cancer. The characteristic feature is that the cancer cells produce a large amount of mucin. This mucin gradually accumulates within the cells, pushing the nucleus to one side and giving the cells a signet-ring-like appearance. Late-stage prostate cancer typically metastasizes to bones, lungs, and other organs via lymphatic or hematogenous routes. Rectal involvement with gastrointestinal symptoms as the initial presenting manifestation is relatively uncommon. This case report aims to describe the diagnostic process of prostate cancer in an 82-year-old male patient. The initial symptom was diarrhea, the admission diagnosis was rectal malignancy, and the diagnostic clue was the presence of signet-ring cells. The tumor origin analysis was conducted alongside serological and imaging examinations. Furthermore, this report discusses the endoscopic manifestations, pathomorphological changes, and clinical prognostic analysis of this prostate cancer case, to enhance the recognition of rare pathological subtypes of prostate cancer.